Narratives of Students’ Digital Literacy Skills: Level of Skills, Actual use of ICTs and Pedagogical Support - Kihwele, Jimmy Ezekiel; Nalaila, Stephano (Journal of Policy and Leadership, 2025)
Various efforts have primarily focused on policy and infrastructure, with little emphasis on instructional approaches to enhance digital literacy preparedness. Thus, the study examined the narratives surrounding students' Digital Literacy Skills and the associated pedagogical approaches aimed at supporting their development. The investigation was limited to Mzumbe University to justify the current initiatives promoting graduates’ 4.0 IR skills. A convergent mixed-method design was employed, utilising interviews, focus group discussions, documentary review and questionnaires for data collection. The study used thematic analysis and descriptive analysis methods to interpret the collected data. Framed by the conceptual framework of 4IR skills (operational and informational skills), the findings reveal that most students rated their ICT operational skills as above average. In contrast, instructors perceived deficiencies in these same skills. The study also reports inconsistent use of ICTs among both students and instructors, which may compromise students’ acquisition of digital literacy skills. Furthermore, this article identifies limited pedagogical practices dedicated to enhancing students’ Digital Literacy Skills for learning at the University and a lack of a clear institutional framework supporting skill development in this domain. Based on these findings, practical and policy implications suggest challenging existing frameworks, such as the 2014 Education and Training Policy (2023 version), the National Digital Education Strategy (2024-2030), the 2016 National ICT Strategy, and the SDGs (4 and 10).